2019
DOI: 10.1101/538348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task errors drive memories that improve sensorimotor adaptation

Abstract: 11Traditional views of sensorimotor adaptation, or adaptation of movements to 12 perturbed sensory feedback, emphasize the role of automatic, implicit correction of 13 sensory prediction errors (differences between predicted and actual sensory 14 outcomes). However, latent memories formed from sensorimotor adaptation, 15 prominently evidenced in improved learning (i.e., savings), have recently been 16 attributed to strategic corrections of task errors (failures to achieve task goals). To 17 dissociate co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…We found that LAS boosted adaptation to sensory prediction errors under no-task-error conditions, particularly at initial exposure to the perturbation. Under standard task error conditions, this effect of LAS might have been masked by task-error driven components of adaptation (such as explicit re-aiming strategies (Mazzoni & Krakauer, 2006) or stimulus-response associations) (Ishii et al, 2018;McDougle & Taylor, 2019;Leow et al, 2020), as it was not discernible under standard task error conditions. In Experiment 2, we further explored the capacity of LAS to influence the retention of sensorimotor memories.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that LAS boosted adaptation to sensory prediction errors under no-task-error conditions, particularly at initial exposure to the perturbation. Under standard task error conditions, this effect of LAS might have been masked by task-error driven components of adaptation (such as explicit re-aiming strategies (Mazzoni & Krakauer, 2006) or stimulus-response associations) (Ishii et al, 2018;McDougle & Taylor, 2019;Leow et al, 2020), as it was not discernible under standard task error conditions. In Experiment 2, we further explored the capacity of LAS to influence the retention of sensorimotor memories.…”
Section: Discussionmentioning
confidence: 96%
“…Participants were assigned to the Standard Task Error LAS group (n=16), Standard Task Error no LAS group (n =16), the No Task Error LAS group (n=16) or the No Task Error no LAS group (n =16). Sample size selection was based on similar work employing task error manipulations (Leow et al, 2020).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent studies have shown that the TE modulates the adaptation rate of the SPE-driven internal model adaptation (Kim et al, 2019) or savings (Leow et al, 2020). This role of the TE as a modulator to the internal model adaptation may suggest a hierarchical interaction rather than parallel interaction between the TE-driven and the SPE-driven motor adaptations.…”
Section: Introductionmentioning
confidence: 94%
“…The interaction between the explicit strategy learning and the internal model adaptation is popularly explained by a two-state model of sensorimotor learning (Smith et al, 2006), where the two operate in parallel and the net adaptation is defined to be the sum of the two (McDougle et al, 2015, Miyamoto et al, 2020). On the other hand, recent studies have shown that the TE modulates the adaptation rate of the SPE-driven internal model adaptation (Kim et al, 2019) or savings (Leow et al, 2020). This role of the TE as a modulator to the internal model adaptation may suggest a hierarchical interaction rather than parallel interaction between the TE-driven and the SPE-driven motor adaptations.…”
Section: Introductionmentioning
confidence: 99%